Hubungan Kecerdasan Spiritual Dengan Kontrol Diri pada Mahasiswa Berasrama Universitas Muhammadiyah Gorontalo - Mohi, Sri Astita; Liputo, Salahuddin; Mursyid, Muhammad; Kum, Thamrin A. (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the relationship between spiritual intelligence and self-control among dormitory students at Muhammadiyah University of Gorontalo. Spiritual intelligence refers to an individual’s ability to understand the meaning of life, values, and self-awareness toward God and others, which is believed to play a role in shaping self-control. This research employs a quantitative approach with a correlational method. The sample consists of 129 dormitory students, determined using the Slovin formula. The instruments used were a spiritual intelligence scale and a self-control scale. Data were analyzed using the Pearson Product Moment correlation test via SPSS 20. The results show a significance value of 0.000 < 0.05 and a correlation coefficient of 0.316, indicating a positive and significant relationship between spiritual intelligence and self-control. This means that the higher the spiritual intelligence, the better the self-control of dormitory students.